IMPROVING STUDENTS’ SPEAKING IN DESCRIBING PEOPLE BY USING THINK-PAIR-SHARE (TPS) TECHNIQUE - Yuliana, Yohanes Gatot Sutapa; Riyanti, Dwi; Ta’dung, Gelbyn (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this research was to improve students’ speaking in describing people by using Think-Pair-Share (TPS) technique. This research a classroom action research which was done in three cycles. The subject for this research was the tenth grade students in class X MIPA 1. The researcher observed students improvement in speaking by collecting data through field notes, observation checklist and speaking test. The students’ attitude towards the learning process was gathered by field note and observation checklist. The data of speaking was obtained by speaking test which was assessed through scoring rubric. The result showed that students’ problems in pronunciation, grammar, vocabulary, fluency and comprehension had been solved by using Think-Pair-Share (TPS) as the teaching technique. Furthermore, students’ interest in speaking especially in describing people also improved. It was shown by the students’ enthusiasm to pay attention in doing every activity during teaching and learning process used Think-Pair-Share (TPS) technique. As the conclusion, the technique was able to be used in improving students’ speaking in descriptive text. The writer recommends the teacher to use Think-Pair-Share (TPS) as a technique in teaching and learning process, especially in the teaching speaking with the similar setting and problems.Key words: Describing People, Speaking, Think-Pair-Share.